Preparation of B4C/CS/SiO2 coating on SS316L for bone implants: Tribological, biological, and antibacterial properties - Zhaobo Wu; Tao Dang; Zhiyuan Zhao; Xiaomeng Xie; Xiaocui Wang; Jun Cao; Minhao Zhu (Friction)
To improve the wear and corrosion resistance, bioactivity, and antimicrobial properties of 316L stainless steel in clinical environment, three kinds of composite coatings of B4C, B4C/chitosan (CS), and B4C/CS/SiO2 were designed and deposited by liquid spraying, respectively. The sliding wear results showed that the B4C/CS/SiO2 coating improves the surface quality under the synergistic effects of boron carbide, chitosan, and silica, and significantly reduces friction coefficients and wear rates. The friction shear force of the B4C/CS/SiO2 coating increases due to its high hardness and elastic modulus, resulting in a high friction coefficient. However, its high hardness and dense internal structure contribute to wear reduction. Friction experiments under simulated body fluid demonstrate that friction coefficient is reduced by calcium and phosphorus. Electrochemical experiments reveal that all three composite coatings significantly reduce the corrosion rate, and the B4C/CS/SiO2 coating exhibits the best anti-corrosion performance. The in vitro mineralization and cell culture experiments demonstrate that the B4C/CS/SiO2 coating has excellent cell proliferation and osteogenic properties, which are attributed to its improved hydrophilicity, increased roughness, and stimulation from Si4+. The antibacterial experiments show that the B4C/CS/SiO2 coating has excellent antibacterial performance, and the antibacterial rate reached 99.58%. Considering all characteristics required for biological applications, the B4C/CS/SiO2 coating demonstrates promising potential for bone implant applications on 316L stainless steel.